XML Schema Representation of DICOM Structured Reporting - Lee, K. P. (American Medical Informatics Association, 2003)
Objective: The Digital Imaging and Communications in Medicine (DICOM) Structured Reporting (SR) standard improves the expressiveness, precision, and comparability of documentation about diagnostic images and waveforms. It supports the interchange of clinical reports in which critical features shown by images and waveforms can be denoted unambiguously by the observer, indexed, and retrieved selectively by subsequent reviewers. It is essential to provide access to clinical reports across the health care enterprise by using technologies that facilitate information exchange and processing by computers as well as provide support for robust and semantically rich standards, such as DICOM. This is supported by the current trend in the healthcare industry towards the use of Extensible Markup Language (XML) technologies for storage and exchange of medical information. The objective of the work reported here is to develop XML Schema for representing DICOM SR as XML documents. Design: We briefly describe the document type definition (DTD) for XML and its limitations, followed by XML Schema (the intended replacement for DTD) and its features. A framework for generating XML Schema for representing DICOM SR in XML is presented next. Measurements: None applicable. Results: A schema instance based on an SR example in the DICOM specification was created and validated against the schema. The schema is being used extensively in producing reports on Philips Medical Systems ultrasound equipment. Conclusion: With the framework described it is feasible to generate XML Schema using the existing DICOM SR specification. It can also be applied to generate XML Schemas for other DICOM information objects.